2017
DOI: 10.1097/won.0000000000000333
|View full text |Cite
|
Sign up to set email alerts
|

Expression of MMP-8 in Pressure Injuries in Spinal Cord Injury Patients Managed by Negative Pressure Wound Therapy or Conventional Wound Care

Abstract: Reduced levels of MMP-8 and an increased rate of healing were found in patients allocated to treatment with a novel negative pressure device as compared to wet to moist gauze conventional dressing. The novel NPWT device used in this study reduced exudate production and enhanced the rate of formation of red granulation tissue.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
14
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 22 publications
0
14
0
Order By: Relevance
“…Except in a sub-set of PUs, the authors did not find any statistically significant differences in the time to closure between the two treatment groups. They found a significant difference in time to closure of PU (mean 10±7.11 days) between the treatment and control groups (27±10.6 days, p=0.05) [1,2,4]. In our study, the reduction in surface area and depth of PUs treated by our NPD was faster than the PUs treated by standard wound care.…”
Section: Discussionmentioning
confidence: 44%
See 2 more Smart Citations
“…Except in a sub-set of PUs, the authors did not find any statistically significant differences in the time to closure between the two treatment groups. They found a significant difference in time to closure of PU (mean 10±7.11 days) between the treatment and control groups (27±10.6 days, p=0.05) [1,2,4]. In our study, the reduction in surface area and depth of PUs treated by our NPD was faster than the PUs treated by standard wound care.…”
Section: Discussionmentioning
confidence: 44%
“…PUs are complex and chronic wounds in patients with SCI and no gold standard has yet been established for their prevention and treatment. PUs are difficult to prevent and manage and can lead to a decline in the overall well-being of patients in SCI [2,4,5,16]. In this study, the novel NPD proposed by us showed a statistically significant improvement in PU healing in terms of reduction in the surface area and depth, slough clearance, granulation tissue formation, and removal of exudate as compared with standard wound care.…”
Section: Discussionmentioning
confidence: 67%
See 1 more Smart Citation
“…Seventeen studies were excluded for the following reasons: did not meet inclusion criteria (n = 5); not an RCT (n = 4); did not describe PIs (n = 4); did not compare with SWC (n = 2); review or case (n = 2). Sixteen studies 26‐41 , which were published from 2002 to 2017 matched the eligibility criteria and were included in the final qualitative study. All the studies consistently reported positive effects of NPWT application.…”
Section: Resultsmentioning
confidence: 99%
“…A range of trials of interventions for PUs appears in the published literature, specifically in people with SCI, some of which may not be captured in existing systematic reviews. Preventative interventions include those which involve self-efficacy enhancement [87] and lifestyle management [88,89], whilst interventions for treatment include irradiation with ultraviolet-C [90], telephone-based support [91] and negative pressure wound therapy [92]. These are clearly candidates for future consideration in systematic reviews and updates.…”
Section: Additional Pu Trials In People With Scimentioning
confidence: 99%